Comparative characteristics of alternative energy sources - Yatsyna, D. S. (ТДАТУ, 2020)
In the course of the comparative analysis, various types of autonomous power plants operating on different principles and from different primary energy sources. The most promising are: solid fuel power plant on local fuel, derivative micro hydroelectric power station, wind farm with vertical axis of rotation and collector solar power plant. These power plants are the most effective in each of their groups; however, when choosing them for autonomous power supply, it is necessary to take into account the specifics of the area for the most optimal result.
Keywords: alternative energy sources are; power plants are; production from renewable sources (RES)